Thyroid Hormone Effects on Mesenchymal Stem Cell Biology in the Tumour Microenvironment - Schmohl, Kathrin Alexandra; Müller, Andrea Maria; Nelson, Peter Jon; Spitzweg, Christine (Experimental and Clinical Endocrinology & Diabetes, 2019)
Non-classical thyroid hormone signalling via cell surface receptor integrin αvβ3, expressed on most cancer cells and proliferating endothelial cells, has been shown to drive tumour cell proliferation and survival, as well as angiogenesis. Tumours develop within a complex microenvironment that is composed of many different cell types, including mesenchymal stem cells. These multipotent progenitor cells actively home to growing tumours where they differentiate into cancer-associated fibroblast-like cells and blood vessel-stabilising pericytes and thus support the tumour’s fibrovascular network. Integrin αvβ3 expression on mesenchymal stem cells makes them susceptible to thyroid hormone stimulation. Indeed, our studies demonstrated – for the first time – that thyroid hormones stimulate the differentiation of mesenchymal stem cells towards a carcinoma-associated fibroblast-/pericyte-like and hypoxia-responsive, pro-angiogenic phenotype, characterised by the secretion of numerous paracrine pro-angiogenic factors, in addition to driving their migration, invasion, and recruitment to the tumour microenvironment in an experimental hepatocellular carcinoma model. The deaminated thyroid hormone metabolite tetrac, a specific inhibitor of thyroid hormone action at the integrin site, reverses these effects. The modulation of mesenchymal stem cell signalling and recruitment by thyroid hormones via integrin αvβ3 adds a further layer to the multifaceted effects of thyroid hormones on tumour progression, with important implications for the management of cancer patients and suggests a novel mechanism for the anti-tumour activity of tetrac.
Keywords: integrin αvβ3; T3; T4; tetrac; angiogenesis; cancer